A Case of Psychosis in Disulfiram Treatment for Alcoholism. (10th April 2014) - Melo, Raquel Calvão de; Lopes, Rui; Alves, José Carlos
Abstract : Background . Disulfiram, a drug used in the treatment of alcohol dependence, is an inhibitor of dopamine- β -hydroxylase causing an increase in the concentration of dopamine in the mesolimbic system. In addition to the physical symptoms associated with concomitant use of alcohol, disulfiram may lead to adverse events, when used alone, including psychosis. Aims . To report a case of a rare complication when using disulfiram for alcoholism treatment in a patient in alcoholic abstinence. Case Report . We describe the case of a 42-year-old male patient, who developed psychotic symptoms 3 weeks after initiating treatment with disulfiram for alcohol dependency. The patient had a history of chronic alcoholism for 12 years and was under disulfiram treatment (250 mg/day) for 1 month, with no other past history of psychiatric illness. The symptoms worsened after he initiated alcohol consumption, while taking disulfiram. The patient was hospitalized and disulfiram was suspended. After 4 days he was asymptomatic and at 6-week follow-up remained asymptomatic. Conclusion . Treatment with disulfiram can lead to the appearance of psychosis in patients with increased vulnerability. In clinical practice, psychosis in the context of alcoholism with disulfiram therapy is often neglected and should be taken into account.